Rebus Story Media: A Study of Effectiveness and Perception in Elementary Arabic Learning - Aslihah, Indy; Fitri, Lailatul; Chikmiyah, Zahrotul; Saputra, Iwanda Yogi (Didaktika Religia, 2025)
This study aims to analyze the effectiveness and students’ perceptions of using Rebus Story media in Arabic language learning at SD NU Insan Cendekia. The research background arises from the low interest and comprehension of students in Arabic vocabulary due to conventional methods that lack visual and contextual engagement. This study employed a mixed methods approach using a convergent parallel design, combining quantitative data from pretest–posttest results and qualitative data from classroom observations and interviews. Statistical analysis revealed that the use of Rebus Story significantly improved students’ learning outcomes, with the mean pretest score of 68.5 rising to 93.25 in the posttest, and a paired-sample t-test result of t(19) = 20.012 (p < 0.001), indicating a highly significant effect. The qualitative findings further showed that students responded positively to the use of this media because it made learning more enjoyable, contextual, and interactive. These results support Mayer’s Cognitive Theory of Multimedia Learning and Paivio’s Dual Coding Theory, emphasizing the importance of combining visual and verbal elements in language learning. The study concludes that Rebus Story is effective in enhancing students’ understanding and motivation in learning Arabic, while also fostering a communicative and collaborative classroom atmosphere.